Velocidade da marcha como preditor de fragilidade em uma amostra populacional de idosos brasileiros - Almeida, Magno Jackson Moreno de (2010)
Gait speed has been described as a predictive indicator of important adverse outcomes in older populations. Among the criteria to evaluate frailty, gait speed has been identified as the most reliable predictor of fragility, practical and low cost. Objective: This study assesses the discriminating capability of gait speed in determining the presence of fragility in the elderly community in northeast of Brazil. Method: We performed an observational analytic study with a transversal character with a sample of 391 community-living elders, aged 65 years or older, of both sexes, in the city of Santa Cruz-RN. Participants were interviewed using a multidimensional questionnaire to obtain sociodemographic information, physical-related and mental health-related information. The unintentional weight loss, muscle weakness, self-reported exhaustion, slow gait and low-physical activity were considered to evaluate the frailty syndrome. Gait velocity was measured as the time taken to walk the middle 4,6 meters of 8,6 meters (excluding 2 meters to warm-up phase and 2 meters to deceleration phase).We calculate the sensitivity and specificity of gait speed test in different cutoff points for the test run time, from which ROC curve was constructed as a measure of test predictive value to identify frail elders. The prevalence of frailty in Santa Cruz-RN was 17.1%. The gait speed test accuracy was 71%when speed is below 0,91m/s. Among women, the gait speed test accuracy was 80%(gait speed below 0.77m/s) and among men, the test accuracy was 86% (gait spend below 0,82%) (p<0,0001).Conclusion: our findings have clinical relevance when we consider that the detection of frailty presence by the gait speed test can be observed in elderly men and women by a simple, cheap and efficient exam